Evaluating Arabidopsis Primary Root Growth in Response to Osmotic Stress Using an In Vitro Osmotic Gradient Experimental System - Selene Píriz-Pezzutto; Mauro Martínez-Moré; Maria Sainz; Omar Borsani; Mariana Sotelo-Silveira (Bio-Protocol)
The root meristem navigates the highly variable soil environment where water availability limits water absorption, slowing or halting growth. Traditional studies use uniform high osmotic potentials, poorly representing natural conditions where roots gradually encounter increasing osmotic potentials. Uniform high osmotic potentials reduce root growth by inhibiting cell division and shortening mature cell length. This protocol describes a simple and effective in vitro system using a gradient mixer that generates a vertical gradient in an agar gel based on the principle of communicating vessels, exploiting gravity to generate a continuous mannitol concentration gradient (from 0 to 400 mM mannitol) reaching osmotic potentials of -1,2 MPa. It enables long-term Arabidopsis root growth analysis under progressive water deficit, improving phenotyping and molecular studies in soil-like conditions.